Does measuring matter? Abdominal girth changes and the need to operate in necrotizing enterocolitis - Caroline M. Lamoutte; Diomel de la Cruz; Faidah O. Badru; Daniel Neal; Janice A. Taylor (Elsevier, 2023)
Introduction: Necrotizing enterocolitis (NEC) is a disease of prematurity resulting in surgery for approximately 30% of patients. Trends in abdominal distention can assist decision-making. There is no defined abdominal girth change that predicts need for surgery. The aim of this study was to determine any relationship between girth change and surgery for NEC. Methods: An IRB-exempt review of NEC patients from 2015 to 2020 at a single institution was performed. Inclusion and exclusion criteria were applied. Demographics, daily largest girth, and laboratory data were recorded. Average daily%girth change was calculated, as was largest%change from first girth of NEC episode. Statistical analysis was performed using Mann-Whitney U tests and ROC curve (p<0.05). Results: 43/178 patients were analyzed. 30% underwent surgery. There was a statistically significant difference in average daily%girth change between medical and surgical patients based on <30 and >30 week gestational age; this significance persisted when analyzing birth weight. Laboratory data was non-contributory. Further subgrouping did not yield appropriate sample sizes for analysis. Threshold to predict surgery was a 1.2% daily girth increase based on ROC analysis. Conclusion: Abdominal girth changes differed significantly between medical and surgical NEC. Establishing a threshold for%change in girth would be valuable for NEC management to assist in surgery decision-making; the value found in this study may be within measurement error. However, any girth increase put the patient at risk for surgery. Abdominal girths should continue to be included in surgical decision-making for premature infants with NEC.